2019
DOI: 10.1007/s40265-019-01217-7
|View full text |Cite|
|
Sign up to set email alerts
|

Once-Daily versus Twice-Daily Tacrolimus in Kidney Transplantation: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Background Tacrolimus is the most commonly prescribed medication in initial immunosuppressive regimens to prevent acute rejection in kidney transplant recipients (KTRs). Tacrolimus was originally available as an immediate-release formulation (IR-Tac) given twice daily. Extended-release tacrolimus (ER-Tac) given once daily was later developed with the expectation of improved medication adherence. Data from observational studies, which compared outcomes between ER-Tac and IR-Tac in different populations of KTRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…A previous systematic literature review compared 12-month post-kidney transplant outcomes between TAC QD and TAC BID in randomized controlled trials and observational studies, with the authors finding no significant differences between the regimens in relation to BPAR, graft survival, or patient survival [ 81 ]. By contrast, a more recent systematic literature and meta-analysis of observational studies revealed a 30% lower risk of BPAR at 12 months with TAC QD compared with TAC BID, with no difference in graft or patient survival or kidney function [ 82 ]. Herein, none of the treatments analyzed was associated with increased (or decreased) mortality risk compared with the reference regimen, Prograf+MPA+CS.…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic literature review compared 12-month post-kidney transplant outcomes between TAC QD and TAC BID in randomized controlled trials and observational studies, with the authors finding no significant differences between the regimens in relation to BPAR, graft survival, or patient survival [ 81 ]. By contrast, a more recent systematic literature and meta-analysis of observational studies revealed a 30% lower risk of BPAR at 12 months with TAC QD compared with TAC BID, with no difference in graft or patient survival or kidney function [ 82 ]. Herein, none of the treatments analyzed was associated with increased (or decreased) mortality risk compared with the reference regimen, Prograf+MPA+CS.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients on teriflunomide showed better adherence than patients using DMF, which may be due to difference in dosing scheme (teriflunomide once daily vs. DMF twice daily). In other therapeutic areas, higher dosing frequency has been associated with lower adherence in several, [17][18][19][20] but not in all, 21,22 studies. In addition, persistence to treatment was also higher with oral agents versus injectables.…”
Section: Treatment Persistencementioning
confidence: 99%
“…On the one hand, non-adherence to Tac remains an underestimated problem; on the other hand, Tac metabolism and PK profiles are increasingly coming into focus 11 , 12 . Once-daily drugs such as ER-Tac can improve treatment adherence, but two recent meta-analyses showed comparable clinical outcomes of ER-Tac and IR-Tac 4 , 13 15 .…”
Section: Introductionmentioning
confidence: 99%